A METHOD TO PRESERVE FISH MUSCLE PIECES AND MINCE FROM SCIAENIDS - CHAKRABARTI, R (Fishery Technology, 2017)
Fish muscle pieces and mince from sciaenids can be preserved for 72 and 48 h respectively at ambient temperature (34Â°C + 4.5) in media containing 8 %NaCl, 0.2 % sodium benzoate and 0.5 % potassium sorbate. Incorporation of 0.1 % sodium bisulphite in this media slightly improved the texture and flavour of minced fish.